Perubahan Konsep Dasar Pendidikan DalamMeng hadapi Tantangan Globalisasi Di Dunia Pendidikan - Ratu Ajeng Galuh Pitaloka; Asbi Sadiki; Gusmaneli (GLOBAL SCIENTS PUBLISHER, 2024)
Global insight is a perspective that arises from the awareness that in life everything is alwaysrelated to the wider world, the global world. Every world of education in Indonesia is impossible toisolate itself from global influences. Educational Institutions have paid attention to every change thatappears in the global world, therefore every Educational Institution needs to pay attention to thecommoninterests.Everyeducationalinstitutionneedstoavoidnarrow,subjective,conventionalthinking and think in a pragmatic way. There are two foundations of thinking in the development ofeducation. The first is the vision of Indonesian education, which is to realize an advanced Indonesiathat is sovereign, independent and has personality through the creation of a Pancasila student profile.Second, in terms of various kinds of educational challenges. Among other things, the teacher is theonly source of knowledge. However, in future directions, teachers become facilitatorsofvarioussources of knowledge. In addition, the current learning conditions focus on face-to-face activities.Meanwhile,inthefuture,learningmustutilizetechnology.Theconceptofglobaleducationemphasizes an inclusive way of thinking, if you don't just want to expand information about globalconnectivity. With global education it is hoped that thequality of human resourceswill furtherimprove. Education is no longer teacher-centered but student-centered. So that the output of educationwillbeabletoimproveitsqualityandbeableto competeinthemidstoftheglobalizationera.